Filimonas effusa sp. nov., isolated from a freshwater river. Issue 3 (25th February 2020) - Chen, Wen-Ming; Chen, Tzu-Ying; Li, Zhi-Hao; Kwon, Soon-Wo; Sheu, Shih-Yi
Abstract : Strain TTM-71 T, isolated from a freshwater river in Taiwan, was characterized using a polyphasic taxonomic approach. Phylogenetic analyses based on 16S rRNA gene sequences and an up-to-date bacterial core gene set (92 protein clusters) indicated that strain TTM-71 T is affiliated with species in the genus Filimonas . The 16S rRNA gene sequence similarity indicated that strain TTM-71 T is closely related to species within the genus Filimonas (94.7–95.5 % sequence similarity) and had a high sequence similarity with Filimonas endophytica SR 2-06 T (95.5 %). Strain TTM-71 T showed 70.3 % average nucleotide identity and 24.9 % digital DNA–DNA hybridization identity with Filimonas lacunae YT21 T . Cells were Gram-stain-negative, aerobic, motile by gliding, rod-shaped and formed beige-colored colonies. Optimal growth occurred at 20 °C, pH 8, and in the presence of 0.5 % NaCl. The major fatty acids of strain TTM-71 T were iso-C15 : 0, iso-C15 : 1 G and summed feature 3 (comprising C16 : 1   ω 7c and/or C16 : 1   ω 6c ). The predominant hydroxy fatty acid was iso-C17 : 0 3-OH. The polar lipid profile consisted of a mixture of phosphatidylethanolamine, four uncharacterized aminophospholipids, one uncharacterized aminolipid, one uncharacterized phospholipid and one uncharacterized lipid. The predominant polyamine was homospermidine. The only isoprenoid quinone was MK-7. Genomic DNA G+C content was 45.6 mol%. On the basis of the polyphasic evidence presented, strain TTM-71 T is considered to represent a novel species of the genus Filimonas, for which the name Filimonas effusa sp. nov. is proposed. The type strain is TTM-71 T (=BCRC 81160 T =LMG 31017 T =KCTC 62871 T ).